Finite Element Simulation Of Aluminium Silicon Carbide Metal Matrix Composite Machining - Ahmad Adli, Muhammad Akmal (2020)
Aluminium Silicon Carbide is one of the metal matrix composite. Drilling and reaming of Al/SiC composites is very challenging. An overall process optimization strategy is very needed for the actual production. This must be based on a deep understanding of the cutting mechanism. Different drill geometry may give different effect on the heat generation and thrust force on bone. Web thickness, point angle and helix angle are the drill geometry factors studied. So, modeling of Al/SiC drilling process by ANSYS to simulate the effect of axial thrust force and heat generation on bone in order to prevent thermal osteonecrosis. Finite element simulation is applied because the process variables are difficult to measure and directly measurable from the cutting process. There are 2 stages of methodology. During stage 1, the purpose is to validate the simulation whether the model valid or not by testing the simulation with available drill bit with straight shank. During stage 2, simulation is preceded with the drill geometry by using the validated model setting. Response surface methodology is used to design the experiment and ANOVA method is used to analysis the data. It was found that there is significant effect on temperature by the drill geometry involved, and not significant effect on thrust force. There are 10 optimized solutions suggested in this study. First solution (31.92% web thickness, 90° point angle, 31.32° helix angle) and second solution (32% web thickness, 90° point angle, 31.33° helix angle) are predicted as highly desirable for the study.